Pengaruh Media Sosial Marketing, Kepercayaan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Produk Eiger Adventure Di Bintara - Muhamad Rokib; Hadita Hadita; Neng Siti Komariah (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
This research aims to determine the partial and simultaneous influence of the independent variables Social Media Marketing, Trust and Product Quality on the dependent variable Costomer Satisfaction of Eiger Adventure Products at Bintara. This type of research uses a quantitative approach. The population in this study has used Adventure Di Bintara products. This research uses an Accidental Sampling sampling technique using a questionnaire distributed to 114 respondents, then the data results are processed using the SPSS 26 data processing application. The research results show that in the partial t test the variables Social Media Marketing and Product Quality have a positive and significant effect on Customer Satisfaction. However, the Trust variable does not have a significant effect on Purchasing Decisions. The results of the f test show that the variables Social Media Marketing, Trust and Product Quality jointly or simultaneously influence customer satisfaction with the Eiger Adventure product at Bintara. However, the Trust variable does not have a significant effect on Purchasing Decisions. The results of the f test show that the variables Social Media Marketing, Trust and Product Quality jointly or simultaneously influence customer satisfaction with the Eiger Adventure product at Bintara.